A Bibliography of Jacques Derrida in Turkish - Artık, Yusuf (Sofist: An International Journal of Philosophy, 2026)
Bibliographic studies constitute one of the fundamental tools required for the smooth progression of academic work and research. As a reliable reference tool that both facilitates and accelerates research, bibliographic studies play a leading role in presenting the body of work on a specific subject in a coherent and organised manner. Although there have been carefully prepared bibliographic studies on Jacques Derrida in Turkish in the past, this work has become necessary from our perspective, given the time that has elapsed since their publication and the emergence of new studies and translations in the literature. The aim of this study is to compile and bring together all works on Derrida produced in Turkey and in Turkish, both past and present. In pursuit of this objective, books, translations, articles and theses published in Turkish have been carefully examined, and a detailed literature review has been conducted. It is hoped that this bibliography of Derrida will provide a list of texts that anyone wishing to reflect on Derrida in Turkish, to embark on a journey of thought and language alongside Derrida, or to conduct research and produce work on Derrida, may consult.
Keywords: Derrida; Turkey; Turkish; Bibliography